Implementation of Border Management Authority in Karimun Regency - Oksep Adhayanto; Indra Bastian Tahir; Nazaki Nazaki; Nurhasanah Nurhasanah; Nanik Rahmawati (Borong Newinera Publisher, 2023)
Based on Law No. 43 of 2008 concerning State Territories, border management authority is divided at the central, provincial and district/city levels. This study discusses the implementation of border management authority in Karimun Regency. Institutional, financial and human resource issues are still issues that greatly influence implementing border management authority in Karimun Regency. The aim of this research is to find out how the Border Management Authority is implemented by the Karimun district government. This type of research is a type of empirical legal research. The approaches used in this research are the statutory approach, the sociological approach and the library approach. The data collection technique used in this study was interview and observation techniques. The data analysis carried out will use qualitative descriptive analysis. There are still several obstacles in implementing the border management authority carried out by the Karimun Regency Regional Government, such as the problem of border management institutions which do not stand alone, thus having an influence on the implementation of coordination and budgeting. The implementation of other authorities is carried out through strategic collaboration with other stakeholders related to border issues.